Clinical Efficacy and Adverse Effects of Antibiotics Used to Treat Mycobacterium abscessus Pulmonary Disease - Chen, Jianhui; Zhao, Lan; Mao, Yanhua; Ye, Meiping; Guo, Qi; Zhang, Yongjie; Xu, Liyun; Zhang, Zhemin; Li, Bing; Chu, Haiqing (Frontiers in Microbiology, 2019)
Treatment of Mycobacterium abscessus pulmonary infection requires long-term administration of multiple antibiotics. Little is known, however, about the impact of each antibiotic on treatment outcomes. A retrospective analysis was conducted to evaluate the efficacy and adverse effects of antibiotics administered in 244 cases of M. abscessus pulmonary disease. Only 110 (45.1%) patients met the criteria for treatment success. The efficacy of treating M. abscessus pulmonary disease continues to be unsatisfactory especially for infections involving M. abscessus subsp. abscessus. Treatment with drug combinations that included amikacin (adjusted odds ratio [AOR], 3.275; 95% CI, 1.221 - 8.788), imipenem (AOR, 2.078; 95% CI, 1.151 - 3.753), linezolid (AOR, 2.231; 95% CI, 1.078 - 4.616) or tigecycline (AOR, 2.040; 95% CI, 1.079 - 3.857) was successful. Adverse side effects affected the majority of patients (192/244, 78.7%). Severe effects that resulted in treatment modification included: gastrointestinal distress (29/60, 48.3%) mostly caused by tigecycline, ototoxicity (14/60, 23.3%) caused by amikacin; and myelosuppression (6/60, 10%) caused mainly by linezolid. In conclusion, the success rate of treatment of M. abscessus pulmonary disease is still unsatisfactory. The administration of amikacin, imipenem, linezolid and tigecycline correlated with increased treatment success. Adverse side effects are common due to long-term, combination antibiotic therapy. Ototoxicity, gastrointestinal distress and myelosuppression are the most severe.